COMPARATIVE ANALYSIS OF POLITENESS STRATEGIES IN RUSSIAN AND ENGLISH: SPEECH ETIQUETTE, REQUESTS, REFUSALS, AND APOLOGIES (Scientific journal of the Fergana State University, 2025)
This paper explores politeness strategies in Russian and English by analyzing speech etiquette and the practical use of various communicative formulas (apologies, requests, and refusals). The study employs a comparative approach and relies on theoretical foundations provided by renowned Russian and foreign linguists such as N.D. Arutyunova, H. Grice, G. Lakoff, J. Culpeper, and others. It demonstrates that differences in politeness between the Anglophone and Russian-speaking cultures arise from historical and sociocultural factors that impact the choice of specific linguistic forms. The most common ways of expressing requests (imperatives, indirect questions, expanded gratitude constructions) are identified, as well as linguistic means that mitigate the assertiveness of speech acts. This paper may be valuable for research in intercultural communication and for teaching Russian and English as foreign languages.